The Influence of Fraud Hexagon on Financial Statement Fraud - Rahmawati, Rahmawati; Lannai, Darwis; Shaleh, Musliha (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the influence of the fraud hexagon elements—pressure, opportunity, rationalization, capability, ego, and collusion—on detecting fraudulent financial statements in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Research Design and Methodology: The research, meticulously designed, focuses on a sample of 52 manufacturing companies listed on the IDX from 2019 to 2021, selected using purposive sampling based on specific criteria. The fraud hexagon elements are measured through variables such as financial targets, changes in directors, political connections, the nature of the industry, auditor changes, and multiple CEO positions. The data analysis is conducted using multiple linear regression to assess the impact of these variables on financial statement fraud. Findings and Discussion: The findings, of significant importance, indicate that financial targets, changes in directors, and CEO duality have a positive and significant effect on fraudulent financial statements, suggesting that these factors increase the likelihood of fraud. The nature of the industry exhibits a negative and significant effect, implying that certain industry characteristics may reduce fraud risk. In contrast, political connections and auditor changes show a negative and insignificant effect, indicating no substantial impact on fraud detection. Implications: The study highlights the importance of considering multiple governance and operational factors when assessing fraud risk. It suggests that firms and regulators should enhance oversight mechanisms, particularly in areas where fraud risk is heightened due to management dynamics or financial pressures.